The Delta Survey workshop : proceedings from conferences held in Alexandria (2017) and Mansoura (2019) - Wahby, Ayman; Wilson, Penelope (Archaeopress Egyptology, 2022)
This volume comprises the proceedings of two conferences organised by the Delta Survey Project held in Alexandria in 2017 and Mansoura in 2019. The papers contain the results of the latest fieldwork from the Nile Delta and Sinai.